Here's the question you clicked on:
tadhanala
√6x + 5 = √53
to remove the x from under the square root sign you must involve the inverse function, the square. isolate the x on the left and square both sides: \[(\sqrt{6x})^2=(\sqrt{53}-5)^2\] the terms being squared on the right are treated as FOIL
take the constant 5 to the right side and then square both sides to get x
x=+-\[sqr{ 78-10\sqrt{53}}/6\]
taking the constant to right side and squaring both sides we get
As in ur question if a√=b√ Then it means that a=b so as in ur question 6x+5=53. solve now